Performance Analysis of an IoT-Based Smart Home System Using Cisco Packet Tracer 9.0 Simulation - Ari Eko Wardoyo; Taufiq Timur Warisaji; Daryanto (JUSTINDO (Jurnal Sistem dan Teknologi Informasi Indonesia), 2026)
The development of the Internet of Things (IoT) has encouraged the implementation of smart home systems to improve comfort, efficiency, and security. However, most previous studies have primarily focused on system design without conducting quantitative performance evaluations. This study aims to analyze the performance of an IoT-based smart home system using Cisco Packet Tracer 9.0 simulation by measuring latency, connection reliability, and command execution success rate. The research method includes problem identification, network topology design, IoT device configuration, and performance testing through a simulation-based approach. Latency testing is conducted using the ping method to obtain the Round Trip Time (RTT), which is then converted into one-way latency. The results show that the system achieves an average latency of 17.18 ms, indicating fast communication response. In addition, connection reliability and command execution success rate both reach 100%, demonstrating a highly stable and reliable system. Therefore, the proposed smart home system is capable of providing optimal communication and control performance within a simulated environment. This study also indicates that Cisco Packet Tracer can be effectively used as an initial evaluation tool for IoT-based systems before real-world implementation.